The effect of photodynamic therapy on retrobulbar blood flow parameters - Tuerkcueoglu, Peykan; Deniz, Nurettin; Koc, Mustafa; Kurt, Julide; Celiker, Uelku (Blackwell Publishing, 2008)
Purpose: To investigate the effect of photodynamic therapy (PDT) on retrobulbar blood flow parameters. Methods :Twenty-four patients with choroidal neovascular membrane of at least four MPS disc area in one eye due to age-related macular degeneration scheduled for PDT were recruited. Peak systolic and end diastolic velocity of ophthalmic, central retinal and posterior ciliary artery of both eyes were measured with colour Doppler imaging and resistivity index were computed before, at the first and fourth weeks following PDT. Results: Following PDT, the mean peak systolic velocity of posterior ciliary artery increased significantly to a value of 31.90 +/- 13.44 at the first (P = 0001), then returned to an insignificant value of 29.95 +/- 13.03 at the fourth week (P = 0.360), when compared with pre-PDT mean measurement (30.16 +/- 13.15). Resistivity index of posterior ciliary artery also increased significantly to a value of 0.740 +/- 0.77 at the first (P = 0.046), then returned to an insignificant value of 0.666 +/- 0.14 at the fourth week (P = 0.407), when compared with pre-PDT mean measurement (0.709 +/- 0.90). All the other measured data (peak systolic velocity, end diastolic velocity, resistivity index of ophthalmic and central retinal artery; end diastolic velocity of posterior ciliary artery of the treated eyes; all colour Doppler imaging measurements of untreated eyes) did not show any significant change at the first and fourth week following PDT, when compared with the pre-PDT values. Conclusion: The peak systolic velocity and resistivity index of the posterior ciliary artery appear to increase in the first week and return to their baseline values at the fourth week following PDT.
Keywords: colour Doppler imaging; photodynamic therapy; retrobulbar blood flow